EXPLORING COMPUTATIONAL THINKING: AN ANALYSIS WITH SCIENCE TEACHERS FROM THE PERSPECTIVE OF ACTOR-NETWORK THEORY - Fornari, Marcelo Batista; Meglhioratti, Fernanda Aparecida; Ferraz, Daniela Frigo (ARACÊ, 2025)
Science Teaching has evolved continuously, driven by several factors, among which the use of Digital Technologies (DT) stands out. Computational Thinking (CT), in turn, can contribute to a deeper understanding of these advances. In this context, this research aims to describe, analyze and discuss, based on the Actor-Network Theory (ANT), the results on the perception of computational thinking by a group of teachers who participated in the training course "Computational Thinking in Science Teaching". This course, promoted by the State University of Western Paraná, through four meetings and 25-hour certification, had the participation of twelve basic education teachers, mostly science teachers from the public network. The results indicate that most of this group of teachers are unaware of the concept of computational thinking and that, even among those familiar with the subject, the answers were limited in articulation with science teaching. These data highlight the importance of promoting training initiatives to train basic education teachers, so that they can understand and apply, in a creative and effective way, computational thinking in the school context, in an integrated way with the various curricular components, especially in science teaching.